A (i)legitimidade da aplicação de medidas de controle do impacto ambiental aos produtos importados: em prol de um comércio internacional sustentável - Tatianna Mello Pereira da Silva (2013)
The present work will investigate the (i)legitimacy of applying fiscal and regulatory measures aimed at controlling the environmental impact throughout a goods life cycle to imported productsby the light of the multilateral trade system.Thereunto, an explanatory qualitative research will be conducted by studying the World Trade Organization (WTO) legal structure, specialized bibliography and paradigmatic cases submitted either to Panels established under the GATT 1947 or the Dispute Settlement Body (DBS). Besides being a remarkably interesting topic, this discussion is increasingly relevant and current to the extent that environmental issues are progressively topping international and domestic agendas, and measures aimed at mitigating and controlling environmental impact are proliferating, many of which may be trade restrictive.In order to investigate the legitimacy of these fiscal and regulatory measures we will first have to recognize the guiding principles and purposes of the multilateral trade system as contained on the preamble of the Marrakesh Agreement, what will be indispensable for a proper interpretation of the WTO agreements. Next, it will be necessary to carryan incursion on the General Agreement on Tariffs and Trade (GATT), where the understanding of the national treatment principle, inserted on art. III, specifically as regards the evolution of the interpretation of the like products concept, and of the exceptions contained on art.XX,will be of special interest.Analogous provisions of the Technical Barriers to Trade (TBT) Agreement, that covers some of the measures under study, will also be subject to analysis. Having a solid doctrinaire and jurisprudential background, the present work will reach the conclusion that there is a trend to consider the application of internal measures of ecological footprint control to imported goods as violation of the national treatment principle, therefore conditioning its legitimacy to the verification of its subsumption to one of art. XX paragraphs. Believing that this trend derives from an insular and distorted interpretation of the WTO agreements, that deviates from its underlining purposes, this work will propose a reformulation of the aim-and-effects approach as an alternative to a more consistent, teleological and systemic interpretation of the national treatment principle.